Interfacing of surfaces with gallium-based liquid metals – approaches for mitigation and augmentation of liquid metal adhesion on surfaces. (December 2020) - Handschuh-Wang, Stephan; Zhu, Lifei; Gan, Tiansheng; Wang, Tao; Wang, Ben; Zhou, Xuechang
Highlights: Introduction to liquid metal repellent and adhesion promoting surfaces. Explanation of underlying mechanisms for repellent and adhesion promoting surfaces. Application of aforementioned mechanisms for specialized patterning techniques. Introduction to stable interfacing of liquid metal with solid metals by diffusion barriers. Gallium-based liquid metals (GLMs) are an emerging class of materials owing to their intrinsic flexibility and intriguing conductivity and have therefore been applied in a wide variety of research fields, such as soft electronics, energy and biomedicine. Due to the atypical liquid stat at and near room temperature GLMs are anticipated to be ideal candidates for replacing high Young's modulus metals for next-generation soft electronics. For the implementation of GLMs in soft electronics the peculiar wetting and adhesion properties of the GLMs, which are partly due to the self-limiting oxide layer, which forms on the GLMs upon exposure to oxygen, have to be considered. In this review, we report on the key parameters affecting wetting and adhesion of GLMs as well as their underlying mechanism. In this regard, it is well-known that surface topography and surface chemistry play a fundamental role in GLM adhesion, yet the influence of other parameters, such as the composition of the liquid metal, additives (particles) and external triggers (force, electric and magnetic fields), is obscure and therefore requires accurate description. This knowledge is leveraged to either obtain highly mobile GLMs, i.e. for reconfigurable electronics, or well-adherend GLMs, i.e. for reliable conductivity of flexible electronics. The ample strategies for enhanced adhesion enable a vast variety of patterning techniques, such as handwriting and printing techniques. Similarly, the combination of lyophilic and lyophobic surfaces is harnessed for patterning techniques. Representative examples include selective wetting techniques and selective plating techniques. In addition, we highlight the inherent challenges of wetting and adhesion in systems where GLMs are interfacing with solid metals and point out potent solutions to overcome the corrosivity of GLMs toward solid metals. Graphical abstract: Image, graphical abstract